Boosting Residential Property Sales with Integrated Marketing Communication Strategies - Harys Kristanto; Savira Arumdini; Muhammad Fardhon (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
The rapid urbanisation and population growth occurring in Indonesia have transformed housing patterns, particularly in suburban regions such as Bekasi Regency. As a satellite city near Jakarta, Bekasi presents a unique setting where accessibility, infrastructure expansion, and economic growth converge to shape residential demand. This study explores how Integrated Marketing Communication (IMC) strategies are experienced and interpreted by developers, marketers, and homebuyers in influencing interest toward residential properties. Using a qualitative approach, data were obtained through in-depth interviews and focus group discussions, and were then analysed thematically with NVivo software. Participants described the growing role of artificial intelligence (AI) and big data analytics in everyday marketing practice—particularly in identifying consumer behaviour patterns, refining message personalisation, and improving digital responsiveness. The narratives also revealed that macroeconomic and policy contexts, such as shifting interest rates, government housing incentives, and credit accessibility, deeply affect how consumers perceive value and trust in property brands. The findings highlight that IMC functions as a relational and interpretive process, enabling trust, emotional resonance, and message coherence across platforms. This study offers contextual insights into how marketing communication, technology adoption, and economic forces intertwine in shaping the lived experiences of Indonesia’s suburban property market.